Opportunistic Salpingectomy: Current Practice in Hospital Setting in Bangladesh - Shermin, Shahana; Noor, Aysha; Semonti, Humaira Shabnam; Jahan, Samsad (Delta Medical College Journal, 2020)
Background: The fimbrial end of the fallopian tube has recently been suggested as the site of origin for epithelial ovarian cancers (EOC). Therefore, a change in practice with opportunistic salpingectomy (OS) at the time of hysterectomy has been advocated for prevention of ovarian cancer in a low-risk population. Objective: The aim of this study was to analyzethe current trend of performing opportunistic salpingectomy during gynaecological surgery for benign indicationsin a tertiary care hospital of Bangladesh. Materials and method: This retrospective observational study was conducted in the Department of Obstetrics & Gynaecology, BIRDEM Women and Children Hospital, Dhaka, Bangladesh from October 2019 to March 2022. All relevant demographic and clinical information of 255 patients undergoing hysterectomy for benign gynaecological disease without involving the ovaries or adnexae were documented from hospital records after exclusion of patients with any gynecologic cancer or having any ovarian or adnexal pathology, and those who underwent hysterectomy due to pregnancy related conditions. Results: Mean age of the patients was 48.71 ± 8.31 years and the highest proportion of patients (49.0%) were in the 41-50 years of age group. Bilateral salpingo-oophorectomy was done in 131 cases (51.4%) with mean age of 51.95 ± 7.99 years and opportunistic salpingectomy was done in 72 cases (28.2%) with mean age of 42.68 ± 3.97 years. The rate of opportunistic salpingectomy statistically increased from 17.39% in 2019 to 36.17% in 2022. Conclusion: As seen throughout the world, the practice of opportunistic salpingectomy for prevention of ovarian cancer has also increased in Bangladesh in recent years. Delta Med Col J. Jul 2020;8(2): 75-82